2022
DOI: 10.3389/fphys.2022.1037230
|View full text |Cite
|
Sign up to set email alerts
|

The mechanosensitive Piezo1 channels contribute to the arterial medial calcification

Abstract: Vascular calcification (VC) is associated with a number of cardiovascular diseases, as well as chronic kidney disease. The role of smooth muscle cells (SMC) has already been widely explored in VC, as has the role of intracellular Ca2+ in regulating SMC function. Increased intracellular calcium concentration ([Ca2+]i) in vascular SMC has been proposed to stimulate VC. However, the contribution of the non-selective Piezo1 mechanosensitive cation channels to the elevation of [Ca2+]i, and consequently to the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…It was reported that Dooku1 selectively inhibited the endogenous Piezo1 channel and Yoda1-induced dilation in aorta (39). Recent study has also found that application of Dooku1 could inhibit arterial medial calcification (40). Therefore, we chose Dooku1 as a useful tool for in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Dooku1 selectively inhibited the endogenous Piezo1 channel and Yoda1-induced dilation in aorta (39). Recent study has also found that application of Dooku1 could inhibit arterial medial calcification (40). Therefore, we chose Dooku1 as a useful tool for in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…Dooku1, a Yoda1 analogue without agonistic effect, reversibly antagonizes Yoda1 activation [ 80 ]. Although, according to the original concept, Dooku1 has an inhibitory effect only on channels activated by Yoda1, several studies report that an antagonistic effect was also observed in the case of constitutively active channels [ 6 , 80 , 81 ]. It is worth mentioning how open Piezo1 channels can be considered constitutively active due to the influence of cells on each other in tissues compared to the measurements performed on individual, isolated cells.…”
Section: Structure and Function Of Piezo1mentioning
confidence: 99%
“…Therefore, articles discussing the role of Piezo channels in different cell types, tissues, and organs both under physiological and pathological conditions follow one another. A significant amount of scientific data is available about the fundamental role of the Piezo1 channel in the development and function of the cardiovascular system [ 2 , 3 , 4 , 5 , 6 ], in the functioning of the pancreas [ 7 ] and the excretory organ system [ 5 ], in the homeostasis of epithelial cells [ 8 , 9 , 10 , 11 ], in innate immunity [ 12 ], as well as in the responses of blood cells to mechanical stimuli [ 13 ]. Although the number of studies related to the locomotor system has increased significantly in recent years, the role of Piezo1 channels in these organs is still far from being precisely clarified.…”
Section: Introductionmentioning
confidence: 99%
“…High shear stress induces expression and activity of Piezo1 upregulation[ 139 ]. And Piezo1 is highly expressed in aortic stiffening tissues or calcifying condition [ 140 , 141 ]. Augmented Piezo1 channel expression [ 140 ], paralleling with Piezo1 activation lead to [Ca 2+ ]i dramatically elevated via Ca 2+ released from mitochondria [ 142 ].…”
Section: Introductionmentioning
confidence: 99%
“…And Piezo1 is highly expressed in aortic stiffening tissues or calcifying condition [ 140 , 141 ]. Augmented Piezo1 channel expression [ 140 ], paralleling with Piezo1 activation lead to [Ca 2+ ]i dramatically elevated via Ca 2+ released from mitochondria [ 142 ]. Then increased [Ca 2+ ]i induces arteries remodeling [ 143 ].…”
Section: Introductionmentioning
confidence: 99%